The Influence Of M13 Bacteriophage On Protein Adsorption Using Anion Exchange Expanded Bed Chromatography - Mohamed @ Mahmood, Masniza (2006)

(untitled)
The adsorption of a model protein Bovine Serum Albumin (BSA) from unclarified feedstock containing M13 bacteriophage and its host cells has been explored. The matrix used was Streamline Diethylaminoethyl (DEAE) as an anion exchanger (ρ=1.2 g/cm3) supplied by Amersham Pharmacia Biotechnology. The UpFront Chromatography column (20 mm i.d) was used as the Expanded Bed Adsorption (EBA) contactor. In this study, M13 bacteriophage carrying an insert (C-WSFFSNI-C) was propagated in bacteria Escherichia coli ER2738. Batch adsorption experiment method using Streamline DEAE as adsorbate was also done to determine the influence in the presence of M13 Bacteriophage and its host cell (E. coli) concentrations at various biomass (0%-15% w/v). The maximum protein adsorption of Streamline DEAE was investigated using batch adsorption. The maximum protein adsorption capacity, qmax, and the dissociation constant, Kd were determined. Moreover, the operating parameters of EBA operation such as the degree of the bed expansion and dynamic binding capacity of different settled bed heights under various biomass concentrations were investigated. In this study, the maximum protein binding capacity of Streamline DEAE, qmax was achieved at 230.03 mg/ml adsorbed. At the lowest M13 bacteriophage and its host cells concentration (5% w/v), the dissociation constant, Kd, of this operation is 36.87 mg/ml. For the batch binding experiment using 10% biomass concentration, qmax of 130.01 mg/ml and a Kd of 16.12 mg/ml was determined. Further increase of the biomass concentration to 15% has caused the qmax of the adsorbent reduced to half of that 5% (w/v) biomass concentration, and the Kd determined is only 9.45 mg/ml. It can be concluded that the higher percentage of M13 bacteriophage and its host cells present in the feedstock, the lower qmax can be achieved. From the analysis of breakthrough curve at 10% which C/Co= 0.1, the dynamic binding capacities of various settled bed height under various biomass concentrations were determined. The value varies between the three models (10 cm, 13 cm and 15 cm settled bed height column) and the highest dynamic binding capacity was obtained at the lowest percentage of M13 bacteriophage and its host cells in the feedstock at the highest settled bed height (15 cm).